The Study of the Impact of English upon the Bangladeshi Learners’ Thought-process - Hossain, E. (University of Jaffna, 2025)
Language is a potent tool of representation and it encapsulates the thoughts, ideas and feelings of a community which uses it as an instrument of handling the world. As a collective memory bank, it cartographs the history, culture, attitudes and thought-process and enables its speaker-community to form concepts and achieve cognitive and conceptual development. English has occupied a very crucial place in Bangladesh side by side with its national language and mother tongue viz. Bengali. Different streams of the education system, such as general education, madrasah education, English medium education and English version education in primary. secondary and tertiary levels are using English as a medium of instruction in different degrees in their pedagogy, and thus, English is treated in varied ways in different streams of education system here. In some streams it is treated as a substitution language and in some other streams it is used as merely a supplementary language of Bengali. However, using mixed methods, this paper will seek to pursue the research question regarding how the diverse roles of English as a medium of instructions impact the cognitive and conceptual development of the learners.
Keywords: Tool; Memory bank; Pedagogy; Thought-process; Medium of instruction